Application of electric boilers for water apartment heat supply - A. L. Toropov (Vestnik MGSU)
Introduction. Apartment heat supply refers to the provision of heat to the heating, ventilation and hot water supply systems of apartments. At the present time, wall convection gas boilers are used as heat generators for apartment heat supply. Comparison of energy, ecological, economic indicators of autonomous heat supply system when replacing gas heat generators with electric ones is given. The issues of equipment safety and costs of service maintenance are considered. Constructive and architectural solutions of equipment placement are proposed.Materials and methods. Official data of Rosstat of the Russian Federation, reports of the Ministry of Energy, the Ministry of Economic Development, current GOSTs and regulatory documents for calculation of heat loss through enclosing structures are used. Calculations were carried out by methods of mathematical modelling.Results. The total power consumption capacity of an apartment household, including electric heat supply, does not exceed 15 kWh. The issue of peak short-term exceeding of the allocated power and the operation of devices for automatic shutdown of household electrical power is solved by setting priority distribution of the allocated power. The carbon intensity of heat power production by electric boilers does not exceed the total average CO2 emission of hydrocarbon fuel heat generators. When using electricity tariffs for houses with electric stoves, the total cost of heat supply by electric boilers does not exceed the standards of payment for district heating of multi-storey buildings. Explosions and gas poisoning are excluded.Conclusions. Autonomous electric heat supply of apartment households has a number of advantages in comparison with apartment heating based on gas heat generators and centralized heating with boilers on gas, coal and liquid fuel. Due to the fact that tariffs for electricity, district heating, gas supply in the regions of the Russian Federation change many times, climatic and environmental conditions are different, it is advisable to calculate the efficiency of the use of electric heat supply separately for each subject of the Russian Federation.